Obitchuary : the big hot book of death - Henry, Spencer (Podcaster); Reyes, Madison; Baker, Allie Kingsley (Plume, 2024)
It's safe to say everyone thinks about death--whether they want to or not. But have you ever wondered about what sort of keepsakes you can make with your remains, or given any thought to the most scandalous deathbed confessions throughout history? Well Madison Reyes and Spencer Henry have, and they've spent countless hours scouring the darkest corners of the internet, digging through newspaper archives, devouring documents, and picking the brains of death industry experts to bring you Obitchuary, a darkly funny and deeply poignant exploration of all things death. With chapters like "Coffin Confessions," "Executions to Die For," "The Last Word," and "If These Dolls Could Speak," Madison and Spencer guide us through surprisingly colorful history, traditions, and contemporary practices. They also demystify taboo topics with incredible and hilarious details, including FUNerals, as they call them, cremations and themed funerals, famous body snatchers, and so much more. Shocking, macabre, hilarious, and moving, Obitchuary digs deep into the physical aspects of death while also carefully exploring what death says about our humanity and the ways we choose to remember those we've lost. So go ahead, crack open the book--we know you're dying to read it.